1998
DOI: 10.1161/01.hyp.32.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance in Hypertension Is Associated With Body Fat Rather Than Blood Pressure

Abstract: Abstract-The insulin resistance syndrome has been characterized by hypertension, upper body obesity, insulin resistance, hyperinsulinemia, glucose intolerance, and hypertriglyceridemia. Previous studies are inconsistent regarding the relationship between blood pressure and insulin resistance. We therefore compared the metabolic profile in 60 hypertensive subjects (meanϮSD arterial pressure, 116Ϯ7 mm Hg) and 60 normotensive subjects (mean arterial pressure, 88Ϯ5 mm Hg) matched for age, gender, and body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 58 publications
1
23
0
2
Order By: Relevance
“…They identified that hypertension was linked to hyperinsulinaemia by obesity. 19 Results from previous studies demonstrated that insulin sensitivity was negatively correlated with obesity in hypertensive patients 3,20 and their family. 21 In the present study, we intend to examine the relations between several anthropometric measures of obesity and insulin sensitivity in Chinese hypertensive patients and their siblings.…”
Section: Discussionmentioning
confidence: 98%
“…They identified that hypertension was linked to hyperinsulinaemia by obesity. 19 Results from previous studies demonstrated that insulin sensitivity was negatively correlated with obesity in hypertensive patients 3,20 and their family. 21 In the present study, we intend to examine the relations between several anthropometric measures of obesity and insulin sensitivity in Chinese hypertensive patients and their siblings.…”
Section: Discussionmentioning
confidence: 98%
“…Both, positive significant relationships and lack of associations between fasting or post-load insulin levels and BP have been reported. 5,[11][12][13][14] For example, in a cross-sectional study, Muller and colleagues 14 demonstrated in 649 white, healthy subjects, a strong association between age, body mass index and waist to hip ratio with systolic BP. No association was observed between the log of fasting insulin or the AUC for the log of insulin levels after a glucose load and systolic BP.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
“…15 A major problem with most of these studies is the poor stratification of the study patients. 5,[11][12][13][14] The presence of confounding variables such as older age, obesity, visceral or abdominal fat accumulation, salt sensitivity, dyslipidaemia and others, complicates the interpretation of the results. Statistical dissection of the data by multiple regression analysis often eliminates most of the observed associations between insulin and BP.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
“…Our results are against the view of a cause-effect relationship between hyperinsulinaemia and hypertension, and of insulin as a major determinant of the subject's BP. [23][24][25] Nevertheless these and other findings, do not rule out the possibility that insulin resistance/hyperinsulinaemia, may play a pathogenetic role in a specific patient's subset, such as the salt-sensitive form of hypertension.…”
Section: Discussionmentioning
confidence: 79%